A Review: Flight Envelope Monitoring and Protection as One of the Flight Safety System - Sarah, Annisa; Prajitno, Prawito; Hasim, Fadillah; Hakim, Teuku Mohd Ichwanul (BRIN Publishing, 2024)
The development of civil aircraft technology, especially commercial aircraft, is now very advanced and complex. This development is intended to assist the pilots to control aircraft in various flight conditions with the main goal to achieved is flight safety. This literature review will discuss research on the flight warning system, which will support the flight envelope protection system development study, which has been conducted over the past few years. The review includes an analysis of existing literature, case studies of aviation accidents, and the evaluation of flight envelope protection systems in current aircraft models. This review shows that the development of technologies and systems can make a significant contribution to flight safety and pilot situational awareness of flight envelope boundaries, so the possibility of aircraft accidents due to loss of control can be reduced